Unity and Diversity in the European Union’s Internal Market Case Law: Towards Unity in ‘Good Governance’? - Mulder, Jotte (Utrecht Journal of International and European Law, 2018)
This article deals with an enduring challenge for the European Court of Justice: striking a balance between the EU market integration requirements and respecting the ‘fundamental structures’ that exist in the Member States through the recognition and accommodation of a range of regulatory options that may restrict trade. The challenge is finding unity in social diversity and many commentators consider that the Court has interpreted the constitutional foundation of the European Union as having turned market access rights into fundamental rights and social policy into an obstructive power that has to be limited. This article reflects on the adjudicative methods of the Court and revisits this debate. It argues that the Court has developed a proportionality assessment that is able to accommodate a plethora of Member State policy choices. Member States’ systems of protection need to be transparent, systematic and internally coherent. However, if these conditions are taken into account, then the level of protection and the means through which this level of protection is sought remain largely at the discretion of the Member States.